Theoretical and practical aspects of professional psychological selection of candidates for training at higher education institutions of the Ministry of Internal Affairs of Ukraine - A. V. Larionova (Law and Safety)
The provision of high-quality professional psychological selection of candidates for higher education with specific learning conditions to improve the professional level of specialists in the police of Ukraine has been studied. Psychological selection as a type of professional selection has been considered in the context of socio-psychological, psycho-physiological and actually psychological normative characteristics of the profession. A systematic analysis of existing approaches to the study of the problem of psychological selection in higher educational institutions of the system of the Ministry of Internal Affairs in science and practice. The author has carried out theoretical and methodological study of the main forms of psychological selection (scientific and methodical, organizational, personnel and logistical), each of them determines the possibility of effective functioning of selection as a system, while having its own methodological, methodical and organizational specifics. The motivational component of professional psychological selection has been studied through the prism of complexity and dynamism of the motivational sphere of personality, as well as the lack of a reliable method of its evaluation. The author has specified and studied three levels of requirements for education in higher educational institutions of the Ministry of Internal Affairs: 1) requirements due to educational activities in the higher educational institutions with specific learning conditions; 2) requirements due to the general features of the law enforcement system; 3) requirements due to the specifics of the future professional activity of an individual in the units of the National Police. Three main stages of psychological selection in the higher educational institutions have been considered (the first is carried out by psycho-diagnostic centers and laboratories at the military medical commission and has a pronounced psychiatric orientation, the second is carried out by the employees of the psychological support service of the Ministry of Internal Affairs of Ukraine in regions, the third is carried out by psychologists of higher educational institutions) and “weak spots” in each of them have been identified. The problems that arise in the scientific and methodological, organizational, personnel and logistical forms of psychological selection of candidates for higher education in the Ministry of Internal Affairs have been determined and researched. The author has offered a number of successive measures to solve them.